Pelatihan Keselamatan Berlalu Lintas sebagai Upaya Preventif Menurunkan Angka Kecelakaan - Budi Mardikawati; Putu Eka Suartawan; Dinda One Mulyaningtyas (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
The number of traffic accidents is still quite high. Human error as a factor causing traffic accidents The purpose of the service is to provide knowledge about safe driving procedures. The method used is socialization directly in the community. The results obtained by the community enable them to understand the subject matter of the knowledge conveyed by the speaker. Armed with this knowledge, participants can better position themselves when driving, so they can drive safely. The implications of the dedication material are that, apart from being for oneself, it is also useful for distributing it to relatives or friends of the participants. The hope is that socialization can reduce the number of accidents caused by human error.